Questions: Suppose H(x)=(9-4x)^7.
Find two functions f and g such that (f∘g)(x)=H(x).
Neither function can be the identity function.
(There may be more than one correct answer.)
f(x)=
g(x)=
Transcript text: Suppose $H(x)=(9-4 x)^{7}$.
Find two functions $f$ and $g$ such that $(f \circ g)(x)=H(x)$.
Neither function can be the identity function.
(There may be more than one correct answer.)
\[
f(x)=
\]
\[
g(x)=
\]
Solution
Solution Steps
Step 1: Understand the composition of functions
We are given \( H(x) = (9 - 4x)^7 \). We need to find two functions \( f \) and \( g \) such that \( (f \circ g)(x) = H(x) \), where neither \( f \) nor \( g \) is the identity function.
Step 2: Break down \( H(x) \) into simpler functions
The function \( H(x) \) can be thought of as a composition of two functions:
A function \( g(x) \) that takes \( x \) and produces \( 9 - 4x \).
A function \( f(x) \) that takes the output of \( g(x) \) and raises it to the 7th power.
Step 3: Define \( g(x) \) and \( f(x) \)
Let \( g(x) = 9 - 4x \). This function is not the identity function because it involves a linear transformation of \( x \).
Let \( f(x) = x^7 \). This function is not the identity function because it involves raising \( x \) to the 7th power.
Step 4: Verify the composition
Now, verify that \( (f \circ g)(x) = H(x) \):
\[
(f \circ g)(x) = f(g(x)) = f(9 - 4x) = (9 - 4x)^7 = H(x).
\]
This confirms that the functions \( f(x) = x^7 \) and \( g(x) = 9 - 4x \) satisfy the condition \( (f \circ g)(x) = H(x) \).